2022
DOI: 10.18103/mra.v10i11.3293
|View full text |Cite
|
Sign up to set email alerts
|

Refutation of the Identity of the Contemporary Official Description of Atherosclerosis with the Real Atherosclerotic Lesions in Humans and Animals

Abstract: The "contemporary official" description of AS, according to the generally accepted theory, should completely coincide with vascular lesions in an animal and vascular lesions in humans. A study of AS in humans and animals has shown that humans have two separate types of lesions that are completely unrelated. Both species have their own characteristics (etiology, pathogenesis, appearance), which are completely different from each other. Lesions in humans also do not coincide with lesions in animals. The "contemp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
37
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(37 citation statements)
references
References 0 publications
0
37
0
Order By: Relevance
“…ASL should be inside the lumen of an artery, should be able to appear very quickly and has nothing to do with perennial inflammation and damage caused to the intima. [38][39][40][41] According to the current view, ASL in humans and animals should be completely identical to each other. The analysis revealed facts that showed a 100% difference between these lesions.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…ASL should be inside the lumen of an artery, should be able to appear very quickly and has nothing to do with perennial inflammation and damage caused to the intima. [38][39][40][41] According to the current view, ASL in humans and animals should be completely identical to each other. The analysis revealed facts that showed a 100% difference between these lesions.…”
Section: Introductionmentioning
confidence: 99%
“…Since ASL in humans and ASL in animals differ by 100%, the possibility of matching characteristics with either ASL in humans or ASL in animals was analyzed. 41 Analysis showed that this type of ASL is absent from both human and animal vessels. As a result of the analysis, it can be assumed that this form of ASL was artificially synthesized to simplify the understanding of the atherosclerotic process and mimic the similarities between processes in animals and two completely different processes in humans.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations